Synthesis of rigid tryptophan mimetics by the diastereoselective Pictet–Spengler reaction of β3‐homo‐tryptophan derivatives with chiral α‐amino aldehydes. (December 2015) - Slupska, Marta; Pulka‐Ziach, Karolina; Deluga, Edyta; Sosnowski, Piotr; Wilenska, Beata; Kozminski, Wiktor; Misicka, Aleksandra
Abstract : The Pictet–Spengler (PS) cyclizations of β 3 ‐ h Trp derivatives as arylethylamine substrates were performed with L‐ α ‐amino and D‐ α ‐amino aldehydes as carbonyl components. During the PS reaction, a new stereogenic center was created, and the mixture of cis/trans 1, 3‐disubstituted 1, 2, 3, 4‐tetrahydro‐ β ‐carbolines was obtained. The ratio of cis/trans diastereomers depends on the stereogenic centre of used amino aldehyde and the size of substituents. It was confirmed by 1H and 2D NMR (ROESY) spectra. The conformations of cyclic products were studied by 2D NMR ROESY spectra. Products of the PS condensation after removal of protecting group(s) can be incorporated into a peptide chain as tryptophan mimetics with the possibility of the β ‐turn induction. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Pictet‐Spengler (PS) cyclizations of β 3 ‐hTrp derivatives were performed withl ‐ and d‐ α ‐amino aldehydes. During the PS reaction, a new stereogenic center was created, and the mixture of cis/trans 1, 3‐disubstituted 1, 2, 3, 4‐tetrahydro‐ β ‐carbolines was obtained. Cyclic products were studied by 1H and 2D NMR spectra. Obtained products can be incorporated into a peptide chain as tryptophan mimetics with the possibility of the β ‐turn induction.